Who was Leonardo da Vinci? - Edwards, Roberta; Kelley, True (New York : Grosset & Dunlap, 2005)
Presents an introduction to the life and accomplishments of the famous Italian Renaissance inventor and artist Leonardo da Vinci.
Who was Leonardo da Vinci? -- An unwanted boy -- The art studio -- The wider world -- Moving on -- Wandering -- The battle of the artists -- Leonardo's ladies -- Losses.
Includes bibliographical references (p. 106).
4.5
3-6
Keywords: Leonardo -- da Vinci -- 1452-1519 -- Juvenile literature; Artists -- Italy -- Biography -- Juvenile literature; Inventors -- Italy -- Biography -- Juvenile literature; Leonardo, -- da Vinci, -- 1452-1519.; Artists; Inventors; Leonardo -- da Vinci -- 1452-1519.; Artists -- Italy -- Biography; Inventors -- Italy -- Biography